Home Industry sebagai Sarana Pemberdayaan Perempuan di Pulau Sabang - Abdillah, Ligar; Sopar, Sopar; Tjoetra, Afrizal; Maifizar, Arfriani (Jurnal Ilmiah Muqoddimah: Jurnal Ilmu Sosial, Politik dan Hummaniora, 2024)
Gender inequality in the work environment is still a problem faced by various countries. This research aims to describe home industry as a means of empowering women to achieve gender equality and women's economic welfare. This research also aims to find common ground between local culture and women's empowerment and identify forms of government support. The benefit of this research is to voice gender equality in accessing economic resources and realizing economic prosperity for women. This research also contributes academically to enriching references for women's empowerment to achieve gender and economic equality. This study is supported by descriptive qualitative methods with data collection techniques through observation and in-depth interviews. The results of this research show that the home industry is very much in line with efforts to empower women to increase access to economic resources and minimize gender inequality. The female workers involved in home industry practices have contributed to fulfilling the family's living needs. Women's empowerment through the AG cake production house is supported by local culture which can show tolerance between religious communities. Even though the owner of the AG cake is a Christian, the production process uses methods and ingredients that do not conflict with the Islamic values of Sabang residents. Granting permits to produce AG cakes is a form of government support that provides legal protection for women's empowerment. This research needs to be continued with research that is able to integrate home industry, women's empowerment, and ecotourism to become a holistic study.